A signalling cascade of IL-33 to IL-13 regulates metaplasia in the mouse stomach. Issue 5 (14th February 2017) - Petersen, Christine P; Meyer, Anne R; De Salvo, Carlo; Choi, Eunyoung; Schlegel, Cameron; Petersen, Alec; Engevik, Amy C; Prasad, Nripesh; Levy, Shawn E; Peebles, R Stokes; Pizarro, Theresa T; Goldenring, James R
Abstract : Objective: Alternatively activated macrophages (M2) are associated with the progression of spasmolytic polypeptide-expressing metaplasia (SPEM) in the stomach. However, the precise mechanism(s) and critical mediators that induce SPEM are unknown. Design: To determine candidate genes important in these processes, macrophages from the stomach corpus of mice with SPEM (DMP-777-treated) or advanced SPEM (L635-treated) were isolated and RNA sequenced. Effects on metaplasia development after acute parietal cell loss induced by L635 were evaluated in interleukin (IL)-33, IL-33 receptor (ST2) and IL-13 knockout (KO) mice. Results: Profiling of metaplasia-associated macrophages in the stomach identified an M2a-polarised macrophage population. Expression of IL-33 was significantly upregulated in macrophages associated with advanced SPEM. L635 induced metaplasia in the stomachs of wild-type mice, but not in the stomachs of IL-33 and ST2 KO mice. While IL-5 and IL-9 were not required for metaplasia induction, IL-13 KO mice did not develop metaplasia in response to L635. Administration of IL-13 to ST2 KO mice re-established the induction of metaplasia following acute parietal cell loss. Conclusions: Metaplasia induction and macrophage polarisation after parietal cell loss is coordinated through a cytokine signalling network of IL-33 and IL-13, linking a combined response to injury by both intrinsic mucosal mechanisms and infiltrating M2 macrophages.